Development of Reflective Practice for Newly Hired Nurses: A Pre-Intervention/Post-Intervention Study - Firdous M. Usman; Syed Ali Bokhari; Maryam H. Darwish (The Journal of Continuing Education in Nursing, 2026)
Background: Reflective practice is essential for nursing professional development, yet its implementation is inconsistent, particularly in non-Western health care systems with diverse international workforces. This study evaluated the immediate impact of a structured educational intervention on reflective practice among newly hired nurses. Method: A total of 16 newly hired nurses at a United Arab Emirates tertiary hospital received a single educational session based on Gibbs' Reflective Cycle. Pre-intervention and post-intervention surveys measured familiarity, understanding, and intent to practice reflection. Optional written reflections were collected within 2 weeks. Results: The intervention significantly improved familiarity with reflective practice (2.21 to 3.64; p < .001) and clarity on writing reflections (2.30 to 4.10; p < .001). Post-intervention, 71.4% reported high confidence. However, only 28.6% submitted written reflections, citing time constraints. Conclusion: Brief structured education significantly enhances understanding of reflective practice, but sustained action requires institutional support, including protected time and mentorship.